Medication use and symptomology in North American women with myalgic encephalomyelitis/chronic fatigue syndrome - Pochakom, Angela; MacNevin, Gillian; Madden, Robyn F.; Moss, Amy C.; Martin, Julia M.; Lalonde-Bester, Sophie; Parnell, Jill A.; Stein, Eleanor; Shearer, Jane (Frontiers in Medicine, 2025)
BackgroundThere are no known curative treatments for myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), and current therapeutic regimens often yield inconsistent results. Despite the profound physical and mental burden experienced by those living with ME/CFS, patients often face a trial-and-error process in finding medications that offer some relief.MethodThe current study surveyed 135 North American women diagnosed with ME/CFS to characterize medication use in relation to disease features, symptomology, and function. Medications were classified into 9 categories according to their primary mechanism of action and therapeutic use.ResultsParticipants were primarily middle-aged (47.1 ± 15.3 years) and were diagnosed for a mean duration of 8.4 ± 9.5 years (mean ± SD). Responses showed 68.6% of participants reported taking medications specifically for ME/CFS. Of those taking ME/CFS-related symptom medications, the average use was 3.0 medications per patient, with higher use in US compared to Canadian participants. Analgesic medications (31.7%) were the most frequently used, followed by psychotropic (26.4%), and immune-related medications (10.6%). These trends persisted across different symptom profiles, apart from gastrointestinal associated medication use replacing immune-related medications in those with gastrointestinal, neurological, and psychiatric symptoms. There was no significant correlation found between the number of medications used with disease duration, age, or age at diagnosis. However, a U-shaped relationship between ME/CFS-related symptom medication use and functional capacity as assessed by self-reported physical movement (hours/week) was evident.ConclusionOur study highlights the diverse and complex patterns in pharmacological treatment regimens for ME/CFS in women, while also underscoring the need for more tailored and evidence-based therapeutic strategies to address the varied symptom profiles.